Evaluation of 100 Meter Sprint Running Skills for Grade X Students of Tunas Bangsa Vocational School - Emayanti Anggraeni; Mukharrar Fadjri; Sandrorium (Universitas Muhammadiyah Sorong, 2025)
This study aims to evaluate the 100-meter sprint running skills of class X students of SMK Tunas Bangsa. The type of research is descriptive. The method used in this study is a survey method with data collection techniques using observation sheets. The population in this study were class X students of SMK Tunas Bangsa. The data collection technique in the study used the total sampling technique, so the number of samples in this study was 30 students. Data analysis used quantitative descriptive which was expressed in the form of a percentage. The results of the study showed that the analysis of the 100-meter sprint running learning outcomes of class X students of SMK Tunas Bangsa was in the